Implication of Nitrogen Application on weed management in Upland rice (Oryza sativa L.) - Kolo, Emmanuel; Adigun, Joseph; Adeyemi, Olusegun; Daramola, Olumide samuel; Bodunde, Goke (Journal of Agricultural Sciences (Belgrade), 2020)
Weed infestation and inherent low soil fertility are among the major factors attributed to the low yield of rice in Nigeria. Field trials were therefore conducted to evaluate the effect of nitrogen application levels and weed control methods on growth and yield of upland rice (var. NERICA 2) at the Teaching and Research Farm of the Federal University of Agriculture, Abeokuta (07o 15’N, 03o 25’E) during 2015-2016 cropping seasons. Three nitrogen (N) levels (0 60 and 90 kg/ha) were evaluated which constituted the main plot treatments, while three weed control treatments viz: pre-emergence application of propanil plus 2, 4-D (Orizo Plus®, Proficol Calle, Baranquilla, Colombia) at 2.0 kg a.i/ha, Orizo Plus® at 2.0 kg a.i/ha followed by supplementary hoe weeding (SHW) at 6 weeks after sowing (WAS) and three hoe weeding at 3, 6 and 9 WAS, and weedy check constituted the sub-plot treatments. All the treatments in different combinations were arranged in a split-plot design with three replicates. Results indicated significant (p≤0.05) increase in weed density and dry matter with increase in N application level from 0 to 60 and 60 to 90 kg/ha. Similarly, crop vigour and plant height increased significantly (p≤0.05) with increasing N application level up to 90 kg/ha. However, 60 and 90 kg N/ha were at par in increasing number of tillers, leaf area index and yield attributes of rice. All the weed control methods reduced weed density and dry matter and increased rice growth and yield significantly (p≤0.05) than the weedy check. Pre-emergence application of Orizo Plus® followed by SHW at 6 WAS and three hoe weeding resulted in significantly (p≤0.05) lower weed density and dry matter, and higher number of tillers, panicle weight and grain yield than sole application of Orizo Plus®. Increasing N application level to 90 kg/ha resulted in significant (p≤0.05) increase in grain yield of rice when weeds were controlled either by pre-emergence application of Orizo Plus® followed by SHW at 6 WAS or three hoe weeding. However, under weedy or poor weed control conditions (Orizo Plus® applied alone) increasing N application from 60 kg/ha to 90 kg/ha did not improve rice grain yield but rather resulted in significant (p≤0.05) increase in weed density and dry matter. These results suggest that Orizo Plus® at 2.0 kg a.i/ha followed by SHW at 6 WAS  integrated with N application at 90 kg/ha is adequate to effectively control weeds and increase rice yield in rainforest-savannah transition zone of Nigeria.